Analisis Pemanfaatan Aplikasi Canva Sebagai Alat Produksi Pesan Visual Oleh Pengelola Humas Universitas Teknologi Sumbawa - Putri Maharani Hafa; Lalu Ahmad Taubih (Indo Publishing, 2026)
The development of digital technology has driven changes in the way organizations convey information to the public. In the higher education environment, visual messages play an important role in delivering information, shaping institutional image, and managing public relations. One of the applications used to support these activities is Canva. This study aims to determine the utilization of the Canva application as a visual message production tool by the Public Relations management of Universitas Teknologi Sumbawa (UTS). This study utilized a descriptive qualitative method. Data were collected through interviews, observation, and documentation with informants involved in managing UTS Public Relations publications. Data analysis was conducted using the visual communication concepts by Adi Kusrianto (2007) and Tinarbuko (2015), focusing on the elements of color, typography, images or illustrations, layout, and symbols or icons. The results showed that Canva is optimally utilized as a visual message production tool to support UTS Public Relations information publications. The use of a Canva Premium account was chosen because it provides high efficiency, practicality, and agility in the content creation process. The application of the five visual communication elements in the final designs was deemed communicative, featuring appropriate color contrast, clear typography (readable), and the ability to maintain the campus brand identity through independent template customization. Based on the research results, it can be concluded that Canva has become an effective and primary supporting instrument for UTS Public Relations in processing and delivering publication messages to the public.